2011
DOI: 10.1007/s00345-011-0799-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled screening trials for prostate cancer using prostate-specific antigen: a tale of contrasts

Abstract: Definitive evidence for or against screening is still lacking, as interim analyses from the ERSPC and PLCO await further follow-up in the years to come.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…For over 2 decades, the prostate specific antigen test (PSA) has been used to screen for prostate cancer (PCA) with controversial outcomes [ 1 - 3 ]. Studies have shown that there is no PSA cutoff that would simultaneously optimize the sensitivity and specificity [ 4 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For over 2 decades, the prostate specific antigen test (PSA) has been used to screen for prostate cancer (PCA) with controversial outcomes [ 1 - 3 ]. Studies have shown that there is no PSA cutoff that would simultaneously optimize the sensitivity and specificity [ 4 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of two recent trials have provided conflicting results with regard to the ability of prostate cancer screening to reduce prostate cancer-specific mortality 1. The Prostate Cancer Intervention versus Observation Trial (PIVOT) goes one step further by attempting to assess the efficacy of radical prostatectomy compared with observation, on overall and prostate cancer specific, survival in patients with localised prostate cancer.…”
Section: Contextmentioning
confidence: 99%
“…9 O rastreio do cancro da próstata com o teste PSA contribui para o aumento da sua incidência no final dos anos 80. 10,11 Este tipo de cancro é possivelmente o que apresenta maior risco de sobrediagnóstico, estimado por Brawley em 50-70%. 12 Apesar do comportamento indolente desses tumores, 90% são tratados com radiação aceitação dos rastreios médicos no género feminino (95,6%) e nos que qualificam a sua saúde como "razoável ou fraca" (96,6%).…”
Section: Introductionunclassified
“…Key words: "Secondary Prevention", "Medical Screenings", "Quaternary Prevention", "Disease Mongering", "Health Literacy" ou cirurgia o que acarreta morbilidade como incontinência urinária, disfunção sexual e efeitos gastrointestinais, em cerca de 15-20% dos casos. 11,13 Num estudo realizado por Wegwarth e Gigerenz, a maioria dos participantes de rastreios oncológicos de rotina refere não ter sido informado acerca do sobrediagnóstico e subsequente tratamento desnecessário. Cerca de 69% afirma não iniciar o rastreio se o sobrediagnóstico for tão elevado como é nos casos da mamografia e teste PSA.…”
Section: Introductionunclassified